Detection of large-scale Ly α absorbers at large angles to the radio axis of high-redshift radio galaxies using SOAR. Issue 1 (3rd September 2018) - Silva, M; Humphrey, A; Lagos, P; Guimarães, R; Scott, T; Papaderos, P; Morais, S G
ABSTRACT: We present an investigation of the properties of the extended Ly α halo and the large-scale ${\rm H\, {\small I}}$ absorbing structures associated with five high-redshift radio galaxies at $z$ > 2, using the Goodman long-slit spectrograph on the SOAR telescope, with the slit placed at large angles (>45°) to the radio axis, to study regions that are unlikely to be illuminated by the active nucleus. Spatially extended Ly α emission is detected with large line widths [full width at half-maximum (FWHM) = 1000–2500 km s −1 ], which although impacted by resonant scattering, is suggestive of turbulent motion. We find a correlation between higher blueshifts and higher FWHM, which is an indication that radial motion dominates the bulk gas dynamics perpendicular to the radio axis, although we are unable to distinguish between outflow and infall scenarios due to the resonant nature of the Ly α line. Extended, blueshifted Ly α absorption is detected in the direction perpendicular to the radio axis in three radio galaxies with minimum spatial extents ranging from ≳27 to ≳35 kpc, supporting the idea that the absorbing structure covers the entire Ly α halo, consistent with being part of a giant, expanding shell of gas enveloping the galaxy and its (detected) gaseous halo.